A Case of Legg-Calvé-Perthes Disease due to Transient Synovitis of the Hip - Tadahiko Ohtsuru; Yasuaki Murata; Yuji Morita; Yutaro Munakata; Yoshiharu Kato (Case Reports in Orthopedics)
Transient synovitis (TS) of the hip develops spontaneously in childhood; it usually has a good prognosis and is a self-limiting disease. However, its pathology is not well known. We describe a case of Legg-Calvé-Perthes disease (LCPD) that seemingly developed due to TS. Even if TS is diagnosed on the basis of the patient’s medical history and imaging findings, physicians should consider the possibility of LCPD and perform a careful observation if joint effusion continues and/or a symptom does not improve within 4 weeks.